Effect of Potassium and Plant Growth Promoting Rhizobacteria on Mung bean Yield - Kiswondo, Sumiarjo (Research and Social Study Institute, 2025)
Background: Mung beans (Vigna radiata L.) are a family of legumes and have great potential to be developed because they are one of the food crops widely consumed by the Indonesian people, market demand continues to increase both domestically and for export. However, according to the Directorate General of Food Crops (2022), in the 2021 annual report, in East Java mung bean production has decreased since 2017 - 2021. Potassium (KNO3) is a useful nutrient to meet plant needs, as well as increase yields and resistance to pests and diseases of mung bean plants. PGPR (Plant Growth Promoting Rhizobacteria) are biological agents around plant roots (rhizosphere) and play an important role in increasing plant growth and development, have a positive effect both directly and indirectly, mobilize the absorption of nutrients by plants and play a role in the fixation of free nitrogen into ammonia that can be absorbed by plants.Aims: The purpose of the study was to determine the effect of potassium and PGPR and the interaction of the two treatments on the yield of mung bean plants (Vigna radiata L).Methods: The research method used a factorial Randomized Block Design (RBD), consisting of two treatment factors and 3 (three) replications. The first factor was Potassium (K), consisting of 3 treatment levels, namely K1: 50 kg KNO3 per hectare, K2: 100 kg KNO3 per hectare, K3: 150 kg KNO3 per hectare. The second factor was PGPR fertilizer (P), consisting of 3 treatment levels, namely P1: 6 ml PGPR per liter of water, P2: 12 ml PGPR per liter of water, and P3: 18 ml PGPR per liter of water. The variables observed were plant height, stem diameter, number of pods, pod weight and dry seed weight.Result: The results of the study showed that there was an interaction between the treatment of potassium 150 kg KNO3 per hectare with PGPR 12 ml/L (K3P2) on the growth and yield of mung bean plants, the height of plants at 45 HST was 39.36 cm, the diameter of the stem at 45 HST was 8.16 mm, the number of pods was 22.33 pieces, the weight of the pods was 91.85 grams, and the weight of the seeds was 65.68 grams. The single factor of potassium treatment of 150 kg KNO3 per hectare (K3) and PGPR 12 ml/L (P2) gave the best effect on the growth of plant height, stem diameter and the results of the number of pods, pod weight and seed weight of mung bean plants.